Land Access Mechanisms and Agrarian Conflicts in A Community Plantation Forest: Case Study from Nagari Air Bangis, West Pasaman Regency - Samsuddin; Dharmawan, Arya Hadi; Mardiana , Rina (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2026)
Conflicts over forest resource control often stem from discrepancies between state policies and local land tenure practices. In West Pasaman Regency, West Sumatra, the government granted a 1,590-hectare concession to a cooperative under the Community Plantation Forest (HTR) scheme, with a legal permit valid for 35 years. However, the land has long been occupied and managed by local communities through Siliah Jariah. Tensions emerged due to the absence of formal recognition of socially legitimate claims made by these communities. This study employed a qualitative approach using a case study method in Pigogah Patibubur. Primary data were collected through in-depth interviews with 11 purposively selected informants and direct field observations. The informants included farmers, the head of the Nagari Customary Council (KAN), a former employee of the ex-timber concession PT SSS, and forestry officials. Secondary data were obtained through the review of official documents. Thematic analysis was used to identify patterns of land access and control based on legal and social aspects of the community. The findings reveal that local communities' social legitimacy conflicts with state-backed legal claims, exacerbated by asymmetrical power relations among actors. This study recommends a more inclusive approach to land conflict resolution, one that considers both formal legal frameworks and the rights of indigenous communities.